Social work with groups comprehensive practice and self-care - Zastrow, Charles; Hessenauer, Sarah L. (Brooks/Cole empowerment series., 2019)
Build effective group leadership skills with the experiential and self-evaluation exercises in SOCIAL WORK WITH GROUPS. The authors discuss topics that are central to understanding group leadership: stages of groups, group dynamics, verbal and nonverbal communication, types of groups, and diversity in groups. With support from this book, your classroom becomes a "lab" where you can experience what it's like to work in and lead many kinds of groups. This edition also emphasizes self-care -- with 30 strategies that you can use to improve your, and your clients', well-being.